Associations between the helpfulness of teacher induction programs, teacher self-efficacy, and anticipated first-year teacher retention - Han, Xiaotian (Frontiers in Psychology, 2023)
First-year teachers need help because they are confronted with various challenges and are more likely to leave the profession within a few years. Studies have demonstrated the efficacy of evidence-based teacher induction programs (TIPs) in enhancing the performance of new teachers and promoting positive student outcomes. However, there has been opposition to this assertion, with some suggesting alternative explanations for the observed effects. This study applied Horn et al's high-quality TIP model as the theoretical framework and employed a non-experimental, correlational design to address the research questions by collecting data from 408 first-year primary school teachers in Shanghai. Correlations and multiple regressions were examined in the study. The results revealed the following: (1) the perceptions of the helpfulness of TIP were not found to correlate significantly with teacher self-efficacy; (2) there was a limited negative correlation (r = −0.142, p < 0.01) between self-efficacy and anticipated retention, suggesting that higher self-efficacy scores were associated with low anticipated retention, contrary to the study's hypothesis; (3) anticipated retention was found to be significantly affected by gender, major, and ratings of TIP. Anticipated retention was found to be significantly affected by gender, major, and ratings of TIP helpfulness. The results, implications, and recommendations are discussed further in the study.